Associations between race and survival in pediatric patients with diffuse large B‐cell lymphoma. (27th January 2021) - Khullar, Karishma; Plascak, Jesse J.; Drachtman, Richard; Cole, Peter D.; Parikh, Rahul R.
Abstract: Background: The purpose of this study was to examine the factors associated with disparities in overall survival (OS) by race in pediatric diffuse large B‐cell lymphoma (DLBCL) patients. Methods: We evaluated clinical features and survival among patients ≤21 years of age diagnosed with stage I–IV DLBCL from 2004 to 2014 from the National Cancer Database (NCDB) using a multivariable Cox proportional hazards model. Results: Among 1386 pediatric patients with DLBCL, 1023 patients met eligibility criteria. In unadjusted analysis, Black patients had a significantly higher overall death rate than White patients (HRBlack vs. White 1.51; 95% CI: 1.02–2.23, p  = 0.041). The survival disparity did not remain significant in adjusted analysis, though controlling for covariates had little effect on the magnitude of the disparity (HR 1.46; 95% CI 0.93–2.31, p  = 0.103). In adjusted models, presence of B symptoms, receipt of chemotherapy, stage of disease, and Other insurance were significantly associated with OS. Specifically, patients with B symptoms and those with Other insurance were more likely to die than those without B symptoms or private insurance, respectively (HR 1.75; 95% CI 1.22–2.50, p  = 0.002) and (HR 2.56; 95% CI, 1.39–4.73, p  = 0.0027), patients who did not receive chemotherapy were three times more likely to die than those who received chemotherapy (HR 3.10; CI 1.80–5.35, p  < 0.001), and patients who presented with earlier stage disease were less likely to die from their disease than those with stage IV disease (stages I–III HR 0.34, CI 0.18–0.64, p  < 0.001; HR 0.50, CI 0.30–0.82, p  = 0.006, HR 0.72, CI 0.43–1.13, p  = 0.152, respectively). Conclusions: Our results suggest that racial disparities in survival may be mediated by clinical and treatment parameters. Abstract : The purpose of this study was to examine the factors associated with disparities in overall survival (OS) by race in pediatric diffuse large B‐cell lymphoma (DLBCL) patients. Black patients had a significantly higher overall death rate than White patients (HRBlack vs. White 1.54; 95% CI: 1.01–2.35, p  =0.044). Our results suggest that racial disparities in survival may be mediated by clinical and treatment parameters.